2016
DOI: 10.1039/c5ra21160c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a resistive switching gallium oxide thin film with a tailored gallium valence state and oxygen deficiency by rf cosputtering process

Abstract: Resistive switching gallium oxide thin films with tailored oxygen deficiency and gallium valence state were fabricated by rf cosputtering of Ga2O3 and Cr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The general belief is that a competition between conduction mechanisms, i.e., electrode limited conduction and bulk limited conduction, produce irreversible electronic states (LRS and HRS) and NDR effect [36][37][38][39]. The intrinsic ionic defects and vacancy controlled trapping and de-trapping of the charge carriers at the interfaces constitute electrode limited conduction, whereas transport of the charge carriers through the insulator/semiconductor sample constitutes the bulk conduction.…”
Section: Methodsmentioning
confidence: 99%
“…The general belief is that a competition between conduction mechanisms, i.e., electrode limited conduction and bulk limited conduction, produce irreversible electronic states (LRS and HRS) and NDR effect [36][37][38][39]. The intrinsic ionic defects and vacancy controlled trapping and de-trapping of the charge carriers at the interfaces constitute electrode limited conduction, whereas transport of the charge carriers through the insulator/semiconductor sample constitutes the bulk conduction.…”
Section: Methodsmentioning
confidence: 99%
“…The Schottky equation and P-F equation were not applicable for NDR regime and above in the S1 segment of I-V curve. Although many metal oxides with M/MO/M structure have shown the coexistence of resistive switching and NDR effect [9,11,31], but the exact mechanism is not clear. Jia et al [20] observed the NDR in negative voltage side of I-V loop.…”
Section: Analysis Of Basic I-v Characteristicsmentioning
confidence: 99%
“…The thin films of transition metal oxides, e.g., Cr 2 O 3 [7], Ga 2 O 3 [8][9], Al 2 O 3 [10], Fe 2 O 3 [11], Ga-doped Fe 2 O 3 [12], Ba 0.7 Sr 0.3 TiO 3 [13], NiO [14], TiO 2 [15][16], and SiO 2 [17] have shown different types of resistive switching, i.e., unipolar, bipolar or abnormal nature.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 The crystalline β-Ga 2 O 3 thin film deposited at 700°C is high insulative, and the resistance of the gallium oxide thin films decreases significantly with decreasing the growth temperatures. For depositing at 500°C, the non-stoichiometric and amorphous gallium oxide thin film shows high conductive, and the I-V characteristic curve clearly reveals a pinched hysteretic loop as sweeping the voltage with a cycle.…”
Section: -4 Guo Et Almentioning
confidence: 99%
“…For introducing oxygen vacancies in the gallium oxide thin film, tuning the ambient atmosphere and the substrate temperature appear to be crucial factors. [15][16][17] Herein, the nonstoichiometric gallium oxide thin films with an abundant oxygen vacancies were obtained at the low a Authors to whom all correspondence should be addressed. -6 Pa without introducing oxygen, using the pulsed laser deposition technology.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%